Russian International Relations in War and Revolution, 1914-22, Book 1: Origins and War, 1914-16 - McDonald, David MacLaren, 1954-; Hughes, Michael, 1961-; Budnit︠s︡kiĭ, O. V.; Schimmelpenninck van der Oye, David (Book collections on Project MUSE., 2020)
"This international, multiauthor collection of essays examines Russian and early Soviet international relations from the Great War's outbreak in August 1914 through the Revolution of 1917 and the Civil War, ending with the Peace of Riga in 1921. Taking a broad definition of international relations, the chapters range from state-to-state diplomacy to NGOs, civil society, commerce and culture"--